Studying the Relationship between Childhood Maltreatment and Inflammatory Biomarkers in Adulthood from a Psychoneuroimmunological Perspective: A Meta-Analysis - Haniyeh zeraatkar; Mohammad Ali Besharat; Reza Rostami; Keyvan Salehi; Rahman Rostamian (پژوهش‌های کاربردی روانشناختی, 2021)
This study was conducted since inflammation is one of the underlying mechanisms of many autoimmune diseases, cardiovascular diseases, type 2 diabetes, etc. The aim of this study is to collect and compare research findings on the relationship between childhood maltreatment and attachment styles with the level of CRP-IL-6 inflammatory markers. A systematic search of Pub Med, Springer, and Elsevier from 2000 to 2019 yielded approximately 30 English-language papers. Finally, 11 papers met the research criteria and were included. In the included studies, a total of 16,867 subjects were screened for CRP inflammatory markers and 6728 subjects were screened for IL-6 markers. And the random effect meta-analysis results show that people who were exposed to abuse as children, childhood maltreatment, or severe stress or psychological trauma had significantly higher baseline CRP (Z = 3.2, 95% CI= 0.05-0.09) and more IL-6 (Z = 3.1, 95%CI = 0.19-3.19) in adulthood. This systematic review suggests that the experience of severe abuse and stress in childhood contributes to the development of preinflammatory conditions in adulthood. Given the sensitivity and importance of this topic, further research is needed to elucidate many intermediary mechanisms.